Pagophagia-Induced Hyponatremia: An Unusual Case - Aydanur Akbaba; Mustafa Bogan; Ceren Karakeçili; Fatma Boğan; Hasan Sultanoglu (Sudan Journal of Medical Sciences)
Hyponatremia occurs when the serum sodium level is below 135 mmol/L. The symptoms include nausea, vomiting, confusion, headache, cardiorespiratory symptoms, profound somnolence or coma, and seizures are observed. Iron deficiency anemia can also cause pagophagia, a Pica subspecies. Although it has been emphasized that electrolyte disturbance may develop due to pagophagia, only a dearth of cases was reported. A 59-year-old male patient was brought to the emergency department with complaints of incoherent speech that started at night, disorientated movements (such as fluttering and climbing), insomnia, restlessness, and confusion. In 2017, he experienced hyponatremia due to pagophagia and a salt-free diet. At the index episode of hyponatremia, he experienced confusion, drowsiness, and sleepiness. It was learned that the patient enjoyed these symptoms.For this purpose, the patient made a habit of eating a completely salt-free diet and consumed plenty of water. Although pagophagia is considered to cause hyponatremia because it causes excessive water intake, there are not enough cases reported. It is to be noted that people develop habits or addiction to things they like.